Implementasi Pengelolaan Kearsipan dalam Menunjang Akuntabilitas Sekolah: Studi Kasus di SMK Negeri 1 Cijulang - Ai Robihatil Milah; Uswatun Hasanah; Ridwan Nurhidayat; Devi Silvia; Dasep Supriatna (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This study aims to determine how the implementation of archival management can improve school accountability at SMK Neegeri 1 Cijulang. The research method used in this research is a case study method with a qualitative approach. The research subjects in this study were the principal, head of facilities and infrastructure, and administrative staff. The results showed that the management of archives at SMK Negeri 1 Cijulang was not optimal, with a lack of space and special officers in the field of archives. However, efforts have been made for archival management, such as training for administrative staff, which shows improvements in archival management. In this study, researchers also found that effective archiving can improve school accountability by facilitating access to information, increasing efficiency and reducing costs. The results of this study are expected to contribute to knowledge about the implementation of archival management in improving school accountability and provide recommendations for improving the quality of archival management at SMK Negeri 1 Cijulang.